Perancangan User Experience Aplikasi Forum Diskusi dan Jual Beli Tanaman Hias berbasis Mobile - Navisa Putri Maulidia; Mahardeka Tri Ananta; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Since the Covid-19 pandemic, the trend of ornamental plants has become increasingly popular and favored by the public. Due to the ongoing Covid-19 pandemic, many MSMEs have difficulty running their businesses. Even during a pandemic like this, many people are interested in ornamental plants to be used as new hobbies or even for collection. An ornamental plant community that uses social media as a forum for interacting, sharing knowledge, and buying and selling ornamental plants. Therefore, research was conducted to design a user experience application for discussion forums and buying and selling of mobile-based ornamental plants that can help community members to discuss, and share knowledge about how to take care of ornamental plants properly, and become a forum for marketing ornamental plants. This research was conducted using the User-Centered Design method which focuses on the user, especially the user's needs. Testing is done by using the UEQ (User Experience Questionnaire) to measure the value of the user experience on the user experience design that has been made. After doing the UEQ test, it was found that the value of attractiveness is 2.23, perspicuity is 2.11, efficiency is 2.28, dependability is 2.15, stimulation is 2.19 and novelty is 2.05. Based on the value obtained, it can be seen that all aspects have an excellent category.